Analisis Rasio Keuangan Untuk Mengukur Kinerja Keuangan Studi Pada PT. Telekomunikasi Indonesia Tbk Periode 2017-2021 - Isma Susanti; Kurniaty Kurniaty; Abdurrahim Abdurrahim (Jurnal Manuhara : Pusat Penelitian Ilmu Manajemen dan Bisnis, 2023)
This study aims to analyze: (1) to evaluate the financial performance of PT Telkom Indonesia Tbk from 2017 to 2021 using various financial ratios. The financial ratios to be used include liquidity ratios, solvency ratios, activity ratios, and profitability ratios. The design of this study uses a quantitative descriptive approach, which means that the data obtained will be analyzed statistically to provide an overview of the company's financial condition. The survey research method was used to collect financial data from PT Telkom Indonesia Tbk. The results of the study show: that the financial performance of PT Telkom Indonesia Tbk for the 2017-2021 period based on ratio analysis (1) the calculation of the liquidity ratio (current ratio and quick ratio) is said to be not good. (2) solvency ratios, such as (debt to asset ratio) are said to be not good, while (debt to equity ratio) can be said to be good. (3) Activity ratios, such as inventory turnover, are good. (4) profitability ratios, such as (return on equity and return on investment) can be said to be not good.